The occurrence of cervical metastases in squamous cell carcinoma ofthe tongue: is there a rationale for bilateral neck dissection in early-stage tumors? - Moratin, Julius; Semmelmayer, Karl; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian; Freier, Kolja; Horn, Dominik (Journal of cranio-maxillofacial surgery, 2019)
Introduction: The aim of this retrospective study was to evaluate the incidence of regional metastases in squamous cell carcinoma (SCC) of the tongue, in order to validate different neck management regime recommendations. Materials and methods: A cohort of 97 patients suffering from primary SCC of the tongue was analyzed in regard to the development of primary and late neck node metastases, considering tumor stage and affected side. Survival analysis was performed to determine the impact of different relevant clinical and pathological factors on overall and progression-free survival. Results: Regional metastases occurred in 29 patients (29.9%). In early-stage tumors (T1 and T2), the rates of primary metastases were 28.6% and 22.4%, respectively. Bilateral cervical metastases are rare but were detected in early-stage cancer in several cases (T1: 2.1%; T2: 11.8%). Conclusion: The development of regional metastases in the ipsilateral and contralateral neck, even in early-stage SCC of the tongue, illustrates the importance of elective bilateral neck dissection in the treatment of affected patients.